Perbaikan Sistem Pemesanan Komponen pada Bagian Produksi Minibus di PT. X - Verdy Sonivelli; Iwan Halim Sahputra (Jurnal Titra, 2022)
PT X is a coachbuilder company that was founded in 1973.  PT X produces two types of vehicle bodies, namely: minibusses and buses. In order to meet consumer demand, the company uses a make to order strategy. The production department plays an important role, and the warehouse department as a supporter of the production department, therefore a good relationship is needed between the two departments, one of which is ordering and shipping components. The system for ordering and delivery of components now, there is no planning for ordering components, which causes a delay in the production process. Improvements were made by creating an ordering and delivery information system for components, also make a support information system for the Microsoft Dynamics GP program that is already used in the company. Support Information system using Microsoft Macro Excel program. The improvements that have been made can accelerate the component ordering process.